PJMHS 2021
DOI: 10.53350/pjmhs211551680
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Psychological Well-being on Athletic Performance of Professional Athletes

Abstract: The purpose of research was to study the effect of psychological well-being on the athletic performance of professional athletes. The present research was a descriptive of causal-comparative type. The statistical population consisted of professional skill level with an experience of 10 years (n=100) were randomly selected. Data collection tools consisted of three questionnaires: Charbonneau exercise performance questionnaire (2001), Reif's psychological well-being questionnaire (1989). To test the hypotheses, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Practicing is one way for athletes with disabilities to reduce anxiety levels when competing. This is in line with research conducted by Baniasadi and Salehian (2021) which revealed that training allows athletes to strengthen their psychological well-being because they can deal with anxiety and stress better.…”
Section: Discussionsupporting
confidence: 91%
“…Practicing is one way for athletes with disabilities to reduce anxiety levels when competing. This is in line with research conducted by Baniasadi and Salehian (2021) which revealed that training allows athletes to strengthen their psychological well-being because they can deal with anxiety and stress better.…”
Section: Discussionsupporting
confidence: 91%
“…Most of the literature on body image, it is focused on testing how physical activity and sport are associated with more positive body image, or how sports and physical activity interventions can be used to improve body image 17 . When we look at the literature, there are many studies that deal with social appearance anxiety 26,27,28,29,8,30 and psychological well-being 31,32,33,34,35,36,37,38,39 with different variables in the context of sports. However, no study has been found in which the relationship between social appearance anxiety and psychological well-being is discussed together in the context of pilates.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous research has discovered factors that may influence the way that different types of anxiety manifest in sports performance, and numerous studies have demonstrated the detrimental effects that sports competitive anxiety has on soccer (Bukhari et al, 2021). In recent research, the spotlight on the mental health of soccer players has gained unprecedented attention, acknowledging the complexity between psychological well-being and athletic performance (Baniasadi & Salehian, 2021) & (Bali et al, 2015). As athletes strive to achieve excellence, the intricate interplay of physiological and psychological factors becomes increasingly evident (Till & Baker, 2020), & (Razali Abdullah et al, 2016.…”
Section: Introductionmentioning
confidence: 99%